Digitalization in Strategic Management Accounting: The Role of Strategic Control Systems, Performance Measurement, and Decision-Making - Sihombing, Putri Sri Desmita; Surbakti, Lidya Primta (JEMBA: Jurnal Ekonomi Pembangunan, Manajemen & Bisnis, Akuntansi, 2026)
This study aims to examine the role of digitalization in strengthening strategic management accounting practices, particularly in the areas of management control systems, performance measurement, and strategic decision-making. The increasing adoption of digital technologies such as big data analytics, artificial intelligence, enterprise resource planning (ERP), and cloud computing has significantly transformed how organizations generate, process, and utilize accounting information. This study employs a Systematic Literature Review (SLR) approach to synthesize findings from 21 peer-reviewed journal articles and one academic book published within the last ten years. The review process involves systematic identification, screening, data extraction, and thematic analysis to ensure a comprehensive and reliable synthesis of existing research. The findings indicate that digitalization enhances the effectiveness of management control systems by improving data integration, real-time monitoring, and coordination across organizational units. In terms of performance measurement, digital technologies contribute to higher accuracy, relevance, and timeliness of performance information, enabling organizations to evaluate outcomes more comprehensively. Furthermore, digitalization strengthens strategic decision-making processes by providing data-driven insights, reducing uncertainty, and supporting proactive managerial actions. However, the study also identifies several challenges, including limitations in digital competencies, system integration issues, and resistance to organizational change, which may hinder the optimal implementation of digital technologies. This study contributes to the strategic management accounting literature by providing an integrated perspective on the impact of digitalization across key organizational functions. Practically, the findings offer insights for managers and policymakers in designing effective digital transformation strategies that align with organizational goals. The study concludes that digitalization serves as a strategic enabler that not only improves operational efficiency but also enhances the overall quality of managerial decision-making in dynamic business environments.